The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1097/btf.0000000000000190
|View full text |Cite
|
Sign up to set email alerts
|

Replacing the Fusion: Conversion of an Ankle Arthrodesis to a Total Ankle Arthroplasty

Abstract: A painful ankle arthrodesis, whether from malunion, nonunion, or the development of adjacent hindfoot arthritis, can be a difficult problem for the patient and treating surgeon. Several surgical options are available, however, conversion of the arthrodesis to a total ankle replacement offers the potential for restoration of some degree of ankle motion, reduced pain, and improved overall patient function. This concept of an ankle arthrodesis takedown to total ankle replacement and the surgical technique are rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Usage of this technology is relatively new and we report its use as a valuable indication in the conversion of ankle fusion nonunion to an ankle replacement, which Schweitzer et al8 described with a different implant. Our case report is in agreement with the recommendations of the Schweitzer paper, and we present these as a case report highlighting these tenets of ankle fusion conversion to replacement with a different implant than that used by Schweitzer and colleagues with excellent clinical results.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Usage of this technology is relatively new and we report its use as a valuable indication in the conversion of ankle fusion nonunion to an ankle replacement, which Schweitzer et al8 described with a different implant. Our case report is in agreement with the recommendations of the Schweitzer paper, and we present these as a case report highlighting these tenets of ankle fusion conversion to replacement with a different implant than that used by Schweitzer and colleagues with excellent clinical results.…”
Section: Discussionmentioning
confidence: 94%
“…Early clinical and cadaveric studies have demonstrated promising outcomes and benefits to using preoperative navigation for total ankle arthroplasty procedures including accurate, precise, and repeatable implant placement and alignment. Furthermore, decreased operative time, blood loss, and cost have also been reported when using patient-specific guides and instrumentation 8,11–14…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ankle arthrodesis, considered as the gold standard of treatments, eliminates ankle joint motion, potentially resulting in bony fracture, malalignment, nonunion, adjacent joint degeneration, and foot pain 15 . TAA has been advocated as an alternative because it preserves ankle joint motion 6,7 , but complications such as fracture, implant loosening, and malalignment often arise 811 . Studies of gait analysis 1214 , cadaveric experiments 15,16 , physical tests, radiological examination, and pain/function scores 17,18 have compared the two surgical treatments regarding the functional outcomes and complications.…”
Section: Introductionmentioning
confidence: 99%